Analisis Laporan Realisasi Anggaran untuk Menilai Kinerja Keuangan Pemerintah Daerah Provinsi Jawa Timur Tahun 2022 – 2024 - Alya Nurhasani; Ade Budi Setiawan; Dea Julfani; Firda Fauziah; Hilman Ariyansyah; Marisa Talia Putri (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
This study aims to analyze the financial performance of the East Java Provincial Government based on the Budget Realization Report (LRA) for the 2022–2024 period. This study is important to assess the effectiveness of revenue achievement and the efficiency of regional expenditure management. The research method used is quantitative descriptive with secondary data in the form of Budget Realization Reports obtained through documentation techniques. Data analysis was performed using financial ratio analysis, namely effectiveness and efficiency ratios. The results show that the revenue performance of the East Java Provincial Government is in the highly effective category, as reflected in the realization of revenue that was able to reach and even exceed the budget target. However, regional expenditure performance is still considered inefficient because the realization of expenditure is close to the set budget. The conclusion of this study shows that even though revenue optimization has been achieved, the local government still needs to improve expenditure control so that regional financial management becomes more efficient in the future.